Pemanfaatan Lectora Inspire dan Plotagon Story Sebagai Media Pembelajaran Interaktif Bahasa Arab - Shefia, Nilla; Ahsanuddin, Mohammad (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research aims to determine the use of interactive media to improve learning outcomes inArabic language learning. This research uses a qualitative approach. The subjects of this researchwere students of the VA MI Rahmat Sa'id Jombang class. The collection technique in this researchis questionnaires and tests, which are then analyzed using qualitative descriptive methods. Theresults of this research show that interactive media can improve student learning outcomes, asseen in the post-test results (87) of students who experienced an increase from the pre-testresults (70). Apart from that, from the results of the student response questionnaire, 11 out of 22students chose that the use of interactive media was very good as a learning medium in class.